Spatial targeting of habitat creation has the potential to improve agri‐environment scheme outcomes for macro‐moths. Issue 6 (11th August 2016) - Alison, Jamie; Duffield, Simon J.; van Noordwijk, Catharina G. E.; Morecroft, Michael D.; Marrs, Rob H.; Saccheri, Ilik J.; Hodgson, Jenny A
Summary: Agri‐environment scheme (AES) interventions are a major avenue for habitat creation and restoration across Europe. To maximize benefits for biodiversity, AES interventions are sometimes spatially targeted relative to existing semi‐natural habitat (SNH). However, the evidence base for effective spatial targeting is deficient; studies until now have collated data across several taxa and regions, resulting in non‐specific advice that is only useful at the regional scale. We present a field study using macro‐moths (Lepidoptera) to test (i) the impact of creating grassland habitat on arable field margins, (ii) how the impact of this type of AES intervention varies according to species specialism and (iii) the potential impact of spatially targeting AES interventions for proximity to semi‐natural chalk grassland (CG). We surveyed macro‐moths on arable fields with and without AES interventions across a range of levels of connectivity to CG. We also surveyed macro‐moths on CG habitat. Macro‐moth abundance was highest on CG and lowest on arable field centres. The benefits of AES interventions were largest for grassland‐associated macro‐moths: abundance was ∼1·4 times higher on AES margins than on control margins for this group. Chalk grassland‐associated macro‐moths only benefited from AES interventions that were close (<1 km) to large areas (>10 ha) of CG habitat. We estimate that clustering AES interventions around CG could lead to a ∼17% increase in CG macro‐moth abundance on arable margins across our sampled region, leading to an overall increase of 2·6% within the sampled region. Synthesis and applications . We provide evidence that for conservation of species associated with a specific type of semi‐natural habitat (SNH), agri‐environment scheme (AES) interventions are most effectively positioned close to that habitat. Our study on macro‐moths in arable fields with and without AES interventions across a range of levels of connectivity to chalk grassland represents a template for the production of tailored spatial targeting advice. We show that optimal positioning of AES habitat creation depends on the extent of SNH in the surrounding landscape as well as the ecology and life history of species being conserved. Abstract : We provide evidence that for conservation of species associated with a specific type of semi‐natural habitat (SNH), agri‐environment scheme (AES) interventions are most effectively positioned close to that habitat. Our study on macro‐moths in arable fields with and without AES interventions across a range of levels of connectivity to chalk grassland represents a template for the production of tailored spatial targeting advice. We show that optimal positioning of AES habitat creation depends on the extent of SNH in the surrounding landscape as well as the ecology and life history of species being conserved.